2011
DOI: 10.1007/s10457-011-9411-6
|View full text |Cite
|
Sign up to set email alerts
|

Testing the shade tolerance of selected crops under Parkia biglobosa (Jacq.) Benth. in an agroforestry parkland in Burkina Faso, West Africa

Abstract: In Western Africa, interactions between trees and agricultural crops are a key element in determining parkland management in an agricultural environment that is rapidly changing. Eggplant (Solanum melongena), chilli pepper (Capsicum annuum), taro (Colocasia esculenta) and pearl millet (Pennisetum glaucum) were tested for their shade tolerance under Parkia biglobosa trees in southcentral Burkina Faso using a split-plot design. Soil characteristics, chlorophyll fluorescence and crop growth and yield were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…However, the lost fruit yields were compensated for by increased crop production under pruned trees. In contrast, if farmers are not allowed to prune trees, one alternative would be to plant shade-tolerant crops beneath tree canopies and sun-loving crops outside the shaded area (Nur Osman et al 2011;Pouliot et al 2012;Sanou et al 2012).…”
Section: Current Status Of Parkland Agroforestry Systemsmentioning
confidence: 99%
“…However, the lost fruit yields were compensated for by increased crop production under pruned trees. In contrast, if farmers are not allowed to prune trees, one alternative would be to plant shade-tolerant crops beneath tree canopies and sun-loving crops outside the shaded area (Nur Osman et al 2011;Pouliot et al 2012;Sanou et al 2012).…”
Section: Current Status Of Parkland Agroforestry Systemsmentioning
confidence: 99%
“…After evaporation, the samples were dried in the oven to a constant weight; the saponin content was calculated as percentage of the starting material. 30,31…”
Section: Estimation Of Saponinsmentioning
confidence: 99%
“…The concentrations of the flavonoids in the extract was extrapolated from standard calibration curve and expressed as milligram rutin equivalent per g of extract (mg RE/g extract). [31][32][33]…”
Section: Estimation Of Total Flavonoid Concentrationmentioning
confidence: 99%
“…From an old experiment on nutrient uptake in tree-crop interaction, Palm (1995) calculated that crops growing under tree canopies captured less than 16% of the available nutrients, demonstrating a low nutrient-use efficiency. On the other hand, Pouliot et al (2012) affirmed that crops growing under shade condition exhibit low nutrient use efficiencies because In Figure 6.3c, maize grain yield under the canopy of trees responded positively to higher frequencies of herbicide. Maize in the open field did not respond much to higher rates of herbicide.…”
Section: Can Agronomy Enhance Tree-crop Facilitation?mentioning
confidence: 80%
“…Jonsson et al (1999) reported neutral effects of scattered trees on crops, suggesting that combined beneficial effects of temperature modifications and soil fertility improvement could neutralize the negative effects from belowground competition and tree shade. Other studies showed that the outcome of tree-crop interaction is negative, neutral or positive depending on crop type (Pouliot et al 2012;Dossa et al 2013;Sinare & Gordon 2015), crop management (Tilander & Ong 1999;Bazié et al 2012;Dossa et al 2013), the amount of seasonal rainfall (Pouliot et al 2012), tree species (Bazié et al 2012;Sinare & Gordon 2015) and tree management (Rao et al 1999;Tilander & Ong 1999;Bayala et al 2002;Bazié et al 2012). For example, Bayala et al (2012) showed that scattered trees generally had a negative impact on maize yield under high potential areas compared with low potential areas.…”
Section: Smallholder Realities and The Myth Of Scattered Trees In Cromentioning
confidence: 99%